2011
DOI: 10.1590/s0066-782x2011005000029
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos hemodinâmicos da sobrecarga ventricular direita aguda experimental

Abstract: Background: Acute right ventricular overload is associated with high morbidity and mortality clinical situations such as: extensive lung resection, pulmonary thromboembolism, lung transplantation and high altitude pulmonary edema. Some points of its pathophysiology remain unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It was found that functional worsening in research studies involving obese rats was associated with changes in the activation of Serca2a through activation of calmodulin kinase 33 . In another area, in evaluating the hemodynamic effects of right ventricular overload promoted by the selective obstruction of the pulmonary vasculature in pigs, the authors found that, despite the intense right ventricular overload promoted by the obstruction of 82.0% of the pulmonary vasculature and the significant increase in pulmonary artery pressure, no severe cardiovascular dysfunction and/or circulatory shock was found during the period studied 34 . Finally, we studied the effects of angiotensin-I and ischemia in the functional recovery in isolated hearts.…”
mentioning
confidence: 99%
“…It was found that functional worsening in research studies involving obese rats was associated with changes in the activation of Serca2a through activation of calmodulin kinase 33 . In another area, in evaluating the hemodynamic effects of right ventricular overload promoted by the selective obstruction of the pulmonary vasculature in pigs, the authors found that, despite the intense right ventricular overload promoted by the obstruction of 82.0% of the pulmonary vasculature and the significant increase in pulmonary artery pressure, no severe cardiovascular dysfunction and/or circulatory shock was found during the period studied 34 . Finally, we studied the effects of angiotensin-I and ischemia in the functional recovery in isolated hearts.…”
mentioning
confidence: 99%
“…In the last three years, we selected five original contributions, regardless of the studies' areas of investigation. During this period, the award was presented to three original articles in the area of arterial hypertension [1][2][3] , three articles on heart failure and cardiomyopathies [4][5][6] , three articles related to cardiovascular surgery [7][8][9] , two articles in basic and experimental research 10,11 , and one article in the areas of arrhythmia 12 , epidemiology 13 , exercise and rehabilitation 14 and coronary failure 15 , respectively.…”
mentioning
confidence: 99%
“…The clinical and echocardiographic results in the immediate and long-term postoperative period of Ebstein's anomaly repair using the cone reconstruction technique were studied by da Silva et al 7 . The two basic and experimental research projects selected, developed by Brito Filho et al 10 and Nascimento et al 11 , included the evaluation of hemodynamic effects of right ventricular overload promoted by selective obstruction of the pulmonary vasculature in pigs 10 and the role of nitric oxide/L-arginine pathway in the vascular response of obese mice on a highfat diet 11 . Finally, the epidemiological study of Fernandes et al 13 evaluated the prevalence of dyslipidemia in 2,720 adult patients and correlated its occurrence with physical exercise in childhood, adolescence and adulthood.…”
mentioning
confidence: 99%